The Role of Museum in an Aging Society - Aedín Mac Devitt; Bonita Bennett; Mathieu Viau-Courville; Nikolas Papadimitriou; Marina Plati; Eleni Markou; Despina Catapoti; Lizette Gradén; Tom O´Dell; Irene Campolmi; Elisabeth Ioannides; Rina Elster Pantalony; et al. (International Council of Museums (ICOM) and Blackwell Publishing Ltd, 2022)
Finland's demographics are set to change dramatically with regards to its growing number of senior citizens. Pori is a mid-sized city with a large ageing population, and is home to a suburb in which 46 per cent of the residents are retirees. This paper focuses on the initiatives undertaken by the museums catering to the elderly population. The aim is to investigate resident expectations versus museum resources, and offer guidelines for promoting equal distribution of culture amongst the older population and including them in the museums’ diverse service offerings.